Seasonal flooding effects on deer in the Mississippi river batture. Issue 5 (31st May 2019) - Jones, Phillip D.; Strickland, Bronson K.; Demarais, Stephen; McKinley, William T.; Ernst, James R.; Klassen, Jessica. A.
ABSTRACT: Effective deer management requires managers to distinguish between the density‐dependent influence of harvest and local environmental factors. The Batture region of the Lower Mississippi River Valley comprises land adjacent to the river that is not protected by the levee system, and is therefore subject to seasonal flooding with potential to influence the morphology and demographics of white‐tailed deer ( Odocoileus virginianus ). Using harvest records of 42, 954 females and 3, 588 males from 61 Batture properties in Mississippi and Louisiana, we created linear regression models of deer body development and recruitment indices to compare the influence of seasonal flooding, harvest rate, growing season weather, and agronomic forage availability during 1988–2016. Overall, deer in the Batture appeared to be more influenced by extrinsic factors than by harvest. Seasonal flooding appeared in every model and generally had stronger effects than weather or harvest variables. Flooding from 1 to 2 years prior, regardless of season, was correlated with greater female body mass, lactation rates, and antler mass of trophy males, possibly reflecting silt deposition effects on soil fertility and promotion of new understory forages. Conversely, current‐year flooding effects were invariably negative, implying direct effects of displacement. Summer flooding was concentrated during late gestation and peak parturition periods, and exhibited the potential to reduce fall lactation rates by 18%. Harvest rates correlated negatively with female body mass and had no correlation with lactation or antler mass. We detected contrasting long‐term trends of decreasing body mass and increasing harvest rate that may reflect deteriorating habitat. Similar to flooding, increased temperatures and rainfall had negative effects for the current year, whereas increased temperatures had positive effects when occurring in the previous year. Surprisingly, annual variation in the amount of soybeans planted appeared in one model only, exhibiting a small positive effect on antler mass. We hypothesize that extensive planting of soybeans in levee‐protected lands just outside the Batture maintained substantial soybean availability despite variation in the amount planted. Given the dominating influence of flooding and weather on deer physical and reproductive parameters in the Batture, these extrinsic variables should be incorporated into the interpretation of harvest data. The common practice of curtailing harvest, particularly female harvest, following years with extensive flooding is likely counterproductive unless intensive flooding occurs during summer. © 2019 The Wildlife Society. Abstract : Physical and reproductive metrics of white‐tailed deer in the Mississippi River Batture are more strongly affected by seasonal flooding and growing season weather than by harvest. Managers should account for environmental influences on body mass and recruitment trends before making harvest recommendations.